Analysis of image quality metric for ROI using image restoration techniques - Sheik, Syed Amma (International Journal of Engineering and Technology, 2014)
Analysis of an image plays vital role in the image processing field, which leads to the inventions of applications in the area of telemedicine, remote sensing via satellites and other spacecrafts, radar, sonar and acoustic image processing etc. This concept is a key factor in research field. One of the common image analysis is use of Region of Interest (ROI) image, which is an effortless way of analyzing images. This paper proposes a method to analyze the Image Quality Metric (IQM) for a ROI based color image. IQM is accomplished by the use of the three image restoration algorithms such as Blind deconvolution algorithm, Wiener Filtering algorithm and Lucy – Richardson algorithm. Keywords: Blind Deconvolution, Lucy Richardson, Point Spread Function, Region of Interest, Image Quality Metric, Wiener Filter.